Relationship between Bullying Stress and Student Learning Outcomes - Arifah, Izzah Rahmi; Farozin, Moh; Fauziah, Mufied (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study is motivated by the prevalence of bullying behavior often found in schools, which negatively impacts victims, particularly causing stress both in the short and long term. Therefore, the aim of this study is to determine whether there is a significant relationship between stress due to bullying and learning outcomes. It employs a quantitative approach using a correlational method, involving 238 grade VIII students. From the population, a sample of 110 students who had experienced bullying was selected using a purposive sampling method. The instrument utilized to measure stress due to bullying was the bullying stress scale developed by the researcher, based on stress aspects according to Sarafino. To assess student learning outcomes, the researcher conducted a documentation study using student report cards. The research hypothesis was tested using Product Moment Correlation analysis. The results revealed a negative correlation coefficient of -0.325 between stress due to bullying and learning outcomes, with a significance value (sig.) of 0.001, which is smaller than the specified significance level. Thus, it can be concluded that there is a significant relationship between the level of stress experienced by students and the level of learning outcomes achieved, indicating that higher levels of stress are associated with lower learning outcomes. Future research could explore the efficacy of intervention programs aimed at reducing bullying-induced stress and improving learning outcomes among students.